(untitled) (Journal of Comparative & International Higher Education, 2024)
This paper examines the underexplored implications of long-term international academic mobility among Turkish academics in the UK, a group not adequately captured by the Black and minority ethnic (BME) category. Within this international context, the study probes how ethnicity, gender, and religion intersect to shape these migrant academics’ experiences while working in the UK. Grounded in social constructivism and employing intersectionality as a theoretical framework, the methodology entails 50 semi-structured interviews analyzed through NVivo to uncover thematic insights. The main finding reveals a "Whiteness threshold" impacting the integration and success of Turkish academics. Those who pass this threshold experience professional recognition and inclusion, while others face discrimination, isolation, and estrangement. This study contributes to comparative and international higher education by challenging the BME framework and advocating for nuanced policy considerations that recognize the diversity of migrant academics’ experiences, highlighting the need for inclusivity and a reassessment of the BME categorization in the UK academic sector.